Validation of the Italian Version of the Dizziness Handicap Inventory, the Situational Vertigo Questionnaire, and the Activity-Specific Balance Confidence Scale for Peripheral and Central Vestibular Symptoms - Colnaghi, Silvia; Rezzani, Cristiana; Gnesi, Marco; Manfrin, Marco; Quaglieri, Silvia; Nuti, Daniele; Mandalà, Marco; Monti, Maria Cristina; Versino, Maurizio (Frontiers in Neurology, 2017)
Neurophysiological measurements of the vestibular function for diagnosis and follow-up evaluations provide an objective assessment, which, unfortunately, does not necessarily correlate with the patients’ self-feeling. The literature provides many questionnaires to assess the outcome of rehabilitation programs for disequilibrium, but only for the Dizziness Handicap Inventory (DHI) is an Italian translation available, validated on a small group of patients suffering from a peripheral acute vertigo. We translated and validated the reliability and validity of the DHI, the Situational Vertigo Questionnaire (SVQ) and the Activities-Specific Balance Confidence Scale (ABC) in 316 Italian patients complaining of dizziness due either to a peripheral or to a central vestibular deficit, or in whom vestibular signs were undetectable by means of instrumental testing or clinical evaluation. Cronbach's coefficient alpha, the homogeneity index, and test-retest reproducibility, confirmed reliability of the Italian version of the three questionnaires. Validity was confirmed by correlation test between questionnaire scores. Correlations with clinical variables suggested that they can be used as a complementary tool for the assessment of vestibular symptoms. In conclusion, the Italian versions of DHI, SVQ and ABC are reliable and valid questionnaires for assessing the impact of dizziness on the quality of life of Italian patients with peripheral or central vestibular deficit.